Do Mature Companies Pay More Dividends? Evidence from Pakistani Stock Market - Afza, Talat; Mirza, Hammad Hassan (Richtmann Publishing, 2011)
Dividend policy is among the most important unresolved issues in modern corporate finance. Several researches have tried tosolve the dividend puzzle yet, the results are inconclusive as to what determines the optimal dividend policy. Present study has analyzedthe impact of firm’s age on its dividend policy. Using the financial data of 120 companies listed at Karachi Stock Exchange (KSE),Pakistan during 2002 to 2007, this study has explored the non-linear relationship of company’s age with dividend policy. A cubic formof model has been designed by using age, age-square and age-cube as independent variables while controlling for leverage and profitability.The estimated results are consistent with maturity hypothesis and free cash flow hypothesis. The study also supports the impact of tradecycle on dividend policy of listed companies of Pakistan. The results are robust to the alternative proxy of dividend policy i.e. dividendintensity.